6-Methoxyquinoline complexes as lung carcinoma agents: induction of oxidative damage on A549 monolayer and multicellular spheroid model - Cadavid Vargas, Juan Fernando (2019)
The aim of this work was to study the antitumor effects and the mechanisms of toxic action of a series of 6-methoxyquinoline (6MQ) complexes in vitro. The Cu(II) and Zn(II) complexes (Cu6MQ and Zn6MQ) are formulated as M(6MQ)₂Cl₂; the Co(II) and Ag(I) compounds (Co6MQ and Ag6MQ) are ionic with formulae [Ag(6MQ)₂]⁺NO₃⁻ and H(6MQ)⁺[Co(6MQ)Cl₃]⁻ (where H(6MQ)⁺ is the protonated ligand). We found that the copper complex, outperformed the Co(II), Zn(II) and Ag(I) complexes with a lower IC₅₀ (57.9 µM) in A549 cells exposed for 24 h. Cu6MQ decreased cell proliferation and induced oxidative stress detected with H₂DCFDA at 40 µM, which reduces GSH/GSSG ratio. This redox imbalance induced oxidative DNA damage revealed by the Micronucleus test and the Comet assay, which turned into a cell cycle arrest at G2/M phase and induced apoptosis. In multicellular spheroids, the IC₅₀ values tripled the monolayer model (187.3 µM for 24 h). At this concentration, the proportion of live/dead cells diminished, and the spheroids could not proliferate or invade. Although Zn6MQ also decreased GSH/GSSG ratio from 200 µM and the cytotoxicity is related to oxidative stress, the induction of the hydrogen peroxide levels only doubled the control value. Zn6MQ induced S phase arrest, which relates with the increased micronucleus frequency and with the induction of necrosis. Finally, our results reveal a synergistic activity with a 1:1 ratio of both complexes in the monolayer and multicellular spheroids.